Colonial statues and their afterlives. Issue 5 (2nd September 2020) - Çelik, Zeynep
ABSTRACT: Statumania invaded Algeria after the 1840s, and later affected Tunisia. Through an art form that contradicted local values, it conveyed charged messages about colonialism and its various missions. Statues of French military, civilian, and religious actors who had served the colonial project in one way of other appeared in the public spaces of cities ranging from Algiers to Tunis, Tlemcen, and Sfax. Focusing on four case studies, this paper traces the history of these statues from the colonial era to the present day. I show how Algerians and Tunisians struggled to deal with their memories of French rule by highlighting three practices applied to the statues: erasure, substitution, and manipulation. I argue that colonial statues were resilient markers of memory and obstinate survivors, imbued with a curious flexibility to take on and reflect different agendas according to changing circumstances. Their ability to express and manoeuver collective memory is associated with the concept of lieu de mémoire, albeit as a highly dynamic notion.